Outdoor thermal performance investigations towards sustainable tropical environment - Abu Bakar, Aniza; Abdul Malek, Nurhayati (2014)
Most of the developing countries lay close to the equatorial line of tropical climates with their cities experiencing rapid urbanizations, population growths and physical changes. These accelerates the changes in their urban landscape, which results among others the urban heat island phenomenon (UHI). The global temperature increment also increases the cooling load, thus more energy is consumed. Attention is given on building design and its technological advancement in energy saving and conservation, not much research are being conducted on the Malaysia’s microclimate and outdoor thermal environment, although they affect the energy consumption of buildings. This paper discusses the approaches adopted in investigating the hot-humid outdoor environment of Malaysia towards understanding how the landscape design is affecting the microclimate. Several past research from ground surfaces effect on the adjacent thermal environment, the impact of landscape setting on the microclimate, to the influence of the physical dimensions of trees in screening the solar radiation are presented. These parameters seem to have direct influence on the outdoor thermal performance. The findings suggested that the landscape settings influence the microclimate of outdoor spaces where high quantity of trees and big tree size seem to lower the ambient temperature. Turfed surfaces seem to lower down the ambient temperature compared to tar-mac surfaces. Several recommendations through design initiatives to mitigate the UHI effects in urban areas are made.